Household recycling behaviour in South Africa: Evidence from the 2018 General Household Survey - de Kock, Samantha (School of Economics, 2021)
This paper is an investigation of the determinants of household recycling behaviour in South Africa. Waste generation around the world is growing exponentially. The proportion of South African households who recycle is very low and landfilling is the primary method of waste disposal. This is problematic because landfilling has a negative impact on the environment and human health. Therefore, alternatives to landfilling, like recycling are necessary. Thus, it is important to understand what determines recycling behaviour. A probit regression analysis was carried out using data from the 2018 General Household Survey in order to understand household recycling behaviour. The results of the regression suggest that age, race, province, urban-rural residence, the presence of a radio in the household, and owning a vehicle are significantly correlated with household recycling behaviour (p<.10). Additionally, gender, marital status and household income are also significantly correlated with household recycling behaviour. However, the relationship is weaker (p<.10). Surprisingly, education, employment, dwelling-type, tenure and the presence of a school child in the household have no effect on recycling participation. These results can help policy-makers understand what factors influence recycling behaviour and help them develop and implement effective policies that optimise recycling activity.